2008
DOI: 10.1007/s15010-008-6303-4
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Abscess likely due to BCG Vaccination in a Child

Abstract: Bacillus Calmette-Guérin (BCG) vaccine has a good safety profile in immune competent children and considerable risks such as disseminated BCG disease in individuals with immune deficiencies. However, some complications including local subcutaneous infection, regional suppurative lymphadenitis may occur after BCG vaccination in immune competent children. A 17-month-old female child was admitted with a painless protruding mass on the anterior chest wall. There was no evidence of previous tuberculous infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…Generally speaking, BCG is considered to be a safe vaccine . Literature search identified five previous reports of tumor caused by BCG infection in immunocompetent patients . Similar to the present case, all patients developed tumors in the chest wall, but only two were confirmed to be caused by BCG on PCR analysis .…”
supporting
confidence: 77%
“…Generally speaking, BCG is considered to be a safe vaccine . Literature search identified five previous reports of tumor caused by BCG infection in immunocompetent patients . Similar to the present case, all patients developed tumors in the chest wall, but only two were confirmed to be caused by BCG on PCR analysis .…”
supporting
confidence: 77%
“…The exact underlying mechanisms of osteomyelitis or abscess development at a site remote from that of M. bovis BCG vaccination have not been identified. Some case reports suggested that hematogenous spread of inoculated bacilli was considered as the underlying mechanisms of M. bovis BCG osteomyelitis or abscess without identified evidence . However, we think that lymphatic transmission cannot be ruled out as the cause of M. bovis BCG costochondritis, because of the combined involvement of both a necrotizing cervical lymph node and costal cartilage, as described in the present study.…”
mentioning
confidence: 43%
“…More rarely, a single sternal focus of osteomyelitis can develop . Other reports described subcutaneous chest wall abscesses due to M. bovis BCG, but there was no involvement of costal cartilage in the 2 cases. The chest wall abscesses were identified relatively late after BCG vaccination, in contrast with osteomyelitis or osteitis, which usually occur 7‐18 months after vaccination .…”
mentioning
confidence: 85%
“…En 2004, le premier cas identifiant une TB cutanée à distance du site d'injection du vaccin a été constaté à Tokyo sur une fillette de six mois [5]. Un second cas a été décrit en Corée sur une fillette âgée de 17 mois, sur la paroi thoracique [6]. D'après la pharmacovigilance et l'ANSM contactées en août 2013, aucun cas d'abcès à distance n'a été notifié en France.…”
Section: Discussionunclassified